Penataan Ruang Hijau Terbuka di Lingkungan Sekolah Dasar Sebagai Bentuk Pendidikan Lingkungan - Rita Sulastini (LPPM UNINUS, 2016)
Program Pengembangan Kota Hijau (P2KH), which since 2011 socialized by the Government, its about sustainalibity development city program with Eco City concept. It all main how to make a good environmental what human need.With the Corporate Social Responsibility (CSR) program which built by the networking beetwen university as educational institution and government or bussinees corporate, hopely bring close to the public. One of the other is make a new rebuilt school environment green open spaces. It press on how far the government or bussinees corporate can built a relationship to make a social educate based on professional responsibility ethics. And how far the educational institution implementation environmental learning for a student.